Corporate Social Responsibility (CSR): Pathway Towards Excellence in Maritime Education and Training (MET) - Alimen, Rolando A.; Cortejo, Nerios S.; Portal, Emily R.; Sepaya, Julian S. (Archives of Business Research, 2023)
This study determined the level of corporate social responsibility (CSR) among faculty members and non-teaching staff of John B. Lacson Foundation Maritime University (JBLFMU)-Molo, Iloilo City, Philippines. The participants in this study were the randomly selected the forty (40) randomly selected employees of John B. Lacson Foundation Maritime University-Molo who were engaged with the university’s corporate social responsibilities (CSRs) for School Year 2018-2019. The present study employed quantitative-qualitative research design. The quantitative-statistical tools used in this study were frequency count, percentage, and rank. Results reveal the following: (1) the level of corporate social responsibility of the respondents was “high,” (2) the respondents agreed that the most dominant corporate social responsibilities (CSRs) were the following: graduates who have good knowledge and high social awareness, taking into consideration that the interest of its students, skills, knowledge, and technology learned inside the classrooms are transferred to the community , (3) significant differences existed in the CSRs when the respondents were grouped according to teaching and non-teaching, (4) five (5) “themes” derived from the qualitative inputs, narrative descriptions, remarks, and views about the CSR at the maritime university (JBLFMU-Molo) were: “sustainability of the programs” in CSR, “help and protect the environment,” “active involvement in CSR,” “regular activities to benefit the society,” and “development of different stakeholders.” Majority of the respondents agreed that CSR is an indicator towards the attainment of excellence in Maritime Education and Training (MET) as a maritime university (JBLFMU-Molo).